2019
DOI: 10.1002/smll.201904523
|View full text |Cite
|
Sign up to set email alerts
|

Magneto‐Ionic Switching of Superparamagnetism

Abstract: Electrochemical reactions represent a promising approach to control magnetization via electric fields. Favorable reaction kinetics have made nanoporous materials particularly interesting for magnetic tuning experiments. A fully reversible ON and OFF switching of magnetism in nanoporous Pd(Co) at room temperature is demonstrated, triggered by electrochemical hydrogen sorption. Comprehensive magnetic characterization in combination with high-resolution scanning transmission electron microscopy reveals the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Hydrogen atoms can diffuse via interstitial sites at high mobility rates (due to their small size), rendering hydrogen-mediated magneto-ionics a very promising approach to circumvent the limited operation speed and cyclability of oxygen magneto-ionics. Hydrogen magneto-ionics have been demonstrated both in solid and liquid [320,335,336,[353][354][355][356][357][358][359] electrolyte configurations. In solid state, Tan et al [336] showed a voltage-induced spin reorientation in Au/GdOx/Co(0.9 nm)/Pt stacks assisted by humid environment, with endurance of up to 2000 cycles, wherein hydrogen accumulation at the GdOx/Co interface caused a modification of the interface magnetic anisotropy.…”
Section: Surface-charged and Magneto-ionic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen atoms can diffuse via interstitial sites at high mobility rates (due to their small size), rendering hydrogen-mediated magneto-ionics a very promising approach to circumvent the limited operation speed and cyclability of oxygen magneto-ionics. Hydrogen magneto-ionics have been demonstrated both in solid and liquid [320,335,336,[353][354][355][356][357][358][359] electrolyte configurations. In solid state, Tan et al [336] showed a voltage-induced spin reorientation in Au/GdOx/Co(0.9 nm)/Pt stacks assisted by humid environment, with endurance of up to 2000 cycles, wherein hydrogen accumulation at the GdOx/Co interface caused a modification of the interface magnetic anisotropy.…”
Section: Surface-charged and Magneto-ionic Materialsmentioning
confidence: 99%
“…Using liquid aqueous electrolyte configuration, Maroun et al demonstrated a reversible increase and decrease of perpendicular coercivity in Pd/Co/Au multilayer stacks arising from hydrogenation of the Pd layer [353]. A transition from superparamagnetic to ferromagnetic behavior [20] was demonstrated in nanoporous Pd(Co) assisted by a Ruderman-Kittel-Kasuya-Yosida-type interaction in the Pd matrix, also due to electrochemical H + reduction to H and subsequent H absorption in this material [357]. Hydrogenbased magneto-ionics was also shown in SrCoO3- [358] and NiCo2O4 films [359].…”
Section: Surface-charged and Magneto-ionic Materialsmentioning
confidence: 99%
“…[31][32][33][34] For such materials, voltageswitching between antiferromagnetic and ferromagnetic or ferrimagnetic states is demonstrated. [32,35] Further, studies on layered composites and nanoporous metal alloys indicate that also many other exciting magnetic phe nomena, such as the exchange bias, [14] spin reorientation, [16,36] and the RKKY interaction [37] length are tunable by electrolytic gating. Although films with uniaxial inplane anisotropy hold great potential for switchable artificial magnetic stray field landscapes for labonachip [38] or for giant magnetoresistance sensors, [39] there are no reports of magnetoionic control of such films yet.…”
Section: Introductionmentioning
confidence: 99%
“…agneto-ionics [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] , i.e., the change in the magnetic properties of materials due to electric field-induced ion motion, is acquiring a leading role, among other magnetoelectric mechanisms (intrinsic 18 or extrinsic 19 multiferroicity, electric charge accumulation [20][21][22], to control magnetism with voltage 23,24 . This is triggered by its capability to largely modulate magnetic properties in a permanent and energy-efficient way 2,25 .…”
mentioning
confidence: 99%